Polyelectrolyte properties of single stranded DNA measured using SAXS and single‐molecule FRET: Beyond the wormlike chain model. Issue 12 (23rd September 2013) - Meisburger, Steve P.; Sutton, Julie L.; Chen, Huimin; Pabit, Suzette A.; Kirmizialtin, Serdal; Elber, Ron; Pollack, Lois; Breslauer, Kenneth J.; Case, David A.; Walter, Nils G.; Woodson, Sarah A.
ABSTRACT Nucleic acids are highly charged polyelectrolytes that interact strongly with salt ions. Rigid, base‐paired regions are successfully described with wormlike chain models, but nonbase‐paired single stranded regions have fundamentally different polymer properties because of their greater flexibility. Recently, attention has turned to single stranded nucleic acids due to the growing recognition of their biological importance, as well as the availability of sophisticated experimental techniques sensitive to the conformation of individual molecules. We investigate polyelectrolyte properties of poly(dT), an important and widely studied model system for flexible single stranded nucleic acids, in physiologically important mixed mono‐ and divalent salt. We report measurements of the form factor and interparticle interactions using SAXS, end‐to‐end distances using smFRET, and number of excess ions using ASAXS. We present a coarse‐grained model that accounts for flexibility, excluded volume, and electrostatic interactions in these systems. Predictions of the model are validated against experiment. We also discuss the state of all‐atom, explicit solvent molecular dynamics simulations of poly(dT), the next step in understanding the complexities of ion interactions with these highly charged and flexible polymers. © 2013 Wiley Periodicals, Inc. Biopolymers 99: 1032–1045, 2013.